Serum Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) Levels in Different Grades of Protein Energy Malnutrition - Chowdhury, Md Serajul Islam; Rahman, ABM Ziaur; Haque, Mahmudul; Nahar, Nazibun; Taher, Abu (Journal of Bangladesh Society of Physiologist, 2008)
The present study was designed to analyze serum AST, ALT levels in different grades of protein energy malnutrition to facilitate early diagnosis, management and rehabilitation of PEM. The serum AST and ALT levels of 50 children of aged 5months to 5 years of both sexes were studied. Among them, 30 children suffering from protein energy malnutrition of 3 different grades were selected for experimental group. Age and sex matched 20 apparently healthy children with no systemic disorder and with weight/height ratio greater than 80% were included in control group. Serum AST and ALT levels were measured by kinetic ultraviolet method according to International Federation of Clinical Chemistry. Data were analyzed statistically by un-paired student 't' test. Mean Serum AST and ALT levels of different grades of protein energy malnutrition were significantly higher (p<0.001) than that of control. Values of mean serum AST and ALT levels were highest in grade-I PEM and it were significantly higher (p<0.001) than both grade-II and grade-III. Again mean serum AST and ALT levels were significantly higher (p<0.001) in grade-II PEM than that of grade-III PEM. The elevated levels of serum AST and ALT is due to tissue break down and hepatobiliary disorder. The results of this study indicate that serum ALT and AST levels are increased in PEM which varies according to its severity. Key Words: Aminotranserase; Malnutrition; Protein DOI:10.3329/jbsp.v2i0.978 J Bangladesh Soc Physiol. 2007 Dec;(2): 17-19.